The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1016/j.actatropica.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Japanese encephalitis in Malaysia: An overview and timeline

Abstract: Japanese encephalitis (JE) is a vector-borne zoonotic disease caused by the Japanese encephalitis virus (JEV). It causes encephalitis in human and horses, and may lead to reproductive failure in sows. The first human encephalitis case in Malaya (now Malaysia) was reported during World War II in a British prison in 1942. Later, encephalitis was observed among race horses in Singapore. In 1951, the first JEV was isolated from the brain of an encephalitis patient. The true storyline of JE exposure among humans an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 61 publications
2
13
0
1
Order By: Relevance
“…Although no report on the Culex spp. in the area of rubber plantation in Malaysia (Kumar et al 2018), the mosquito species are high in Thailand in the rubber plantations and forest areas. A study by Sumodan et al (2005) state that Culex vishnui were found in the Kanchanaburi and Khon Kaen in rubber plantations area.…”
Section: Geographical Distributionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although no report on the Culex spp. in the area of rubber plantation in Malaysia (Kumar et al 2018), the mosquito species are high in Thailand in the rubber plantations and forest areas. A study by Sumodan et al (2005) state that Culex vishnui were found in the Kanchanaburi and Khon Kaen in rubber plantations area.…”
Section: Geographical Distributionmentioning
confidence: 99%
“…Besides that, Pulau Tengah, Johor and Kapar Energy Ventures, Selangor which located in the west coast of Peninsular Malaysia are known as the popular locations for the landing areas of migratory birds. Migratory birds that land at Kapar, Selangor have higher water bodies for the mosquitoes breeding (Kumar et al 2018). Most of the shorebirds are the potential sources of Flavivirus including WNV and JEV.…”
Section: Potential Risk Factors Of Wnv In Malaysiamentioning
confidence: 99%
See 3 more Smart Citations